Marine radionuclide transport modelling: Recent developments, problems and challenges. (December 2019) - Periáñez, R.; Bezhenar, R.; Brovchenko, I.; Duffa, C.; Iosjpe, M.; Jung, K.T.; Kim, K.O.; Kobayashi, T.; Liptak, L.; Little, A.; Maderich, V.; McGinnity, P.; et al.
Abstract: A brief overview of the current status on the subject of numerical modelling of radionuclide transport in the marine environment is given: main transport processes occurring in the sea, basic approaches to solve such processes numerically, up-to-date trends to deal with water/sediment interactions (in the case of non-conservative radionuclides), and topics in which work is currently in progress (like the integration of biological uptake models within marine transport models). A brief review of models applied to simulate Fukushima Daiichi nuclear power plant releases in the Pacific Ocean after the 2011 accident is also included, since the most recent modelling efforts have been focused in this problem. A discussion of the main sources of uncertainty in models is given, as well as the problems these uncertainties pose in relation to emergency modelling, which is one of the most relevant applications of dispersion models. Highlights: Types of marine transport models presented. Present trends to describe water/sediment interactions and other processes commented. Main sources of uncertainties in models described. Opinion given on the use of emergency models to support decision-making.